PENGARUH PERCEIVED VALUE, LIFE STYLE,MOTIVASI, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE DI PEKALONGAN - Sulistiamah Donawati; Teguh Purwanto (MANAJEMEN DEWANTARA, 2026)
This study aims to examine the effect of perceived value, lifestyle, motivation, and brand image on purchasing decisions of iPhone smartphones in Pekalongan. The research is based on consumer behavior theory which explains that purchasing decisions are influenced by psychological and personal factors such as perceived value, lifestyle, motivation, and brand image. The study seeks to identify which variables significantly influence consumer purchasing decisions toward iPhone products. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed online via Google Forms to 126 respondents who are iPhone users in Pekalongan using purposive sampling technique. The data analysis method used is Structural Equation Modeling (SEM) with SmartPLS 4.1.1.6 software. Measurement of responses was conducted using a Likert scale to evaluate respondents’ perceptions of the research variables. The results show that lifestyle, motivation, and perceived value have a positive and significant effect on purchasing decisions of iPhone smartphones in Pekalongan. Among these variables, motivation has the strongest influence on purchasing decisions. Meanwhile, brand image does not have a significant effect on purchasing decisions. The findings indicate that consumers tend to consider functional benefits, personal needs, and lifestyle compatibility rather than brand image when deciding to purchase an iPhone smartphone.